Hippocampal-dependent memory deficit induced by perinatal exposure to polutted eels in middle-aged offspring mice: Sex differential effects. (5th October 2017) - Soualeh, Nidhal; Soulimani, Rachid; Bouayed, Jaouad
Highlights: Impact of maternal polluted eel consumption on cognition of middle-aged mice. Sex and dose dependent effects of the highest polluted eels on memory deficit. Memory deficit programming in females exposed to the highest polluted eels. Exacerbate cytokine production in microglia across the lifespan of males and females. Sensitized microglia might contribute to memory deficit during brain aging process. Abstract: The effects of perinatal exposure to low, intermediate, or highly polluted eels on neonatal, postnatal, adult and middle-aged brain inflammation, and on cognitive performances of middle-aged offspring mice were compared to those of offspring controls. Inflammatory markers in microglia were assessed in offspring on the postnatal days–PNDs 1, 21, 100 and 330. Activated p38MAPK, ERK-1/2 and p65, and acetylcholine levels were assessed in the middle-aged hippocampus. Plasma myeloperoxidase and corticosterone levels were evaluated at PND 330. Learning and its retention, and working memory in middle-aged offspring were assessed using the Morris water maze, and Y-maze. Our results showed enhanced microglia production of inflammatory markers across the lifespan of male as well as female exposed offspring. Inflammation and increased p38 MAPK activation were detected in the exposed middle-aged hippocampus of both exposed sexes. Significant levels of MPO, but not corticosterone, were found in middle-aged males and females perinatally exposed to eels. However, decreases in ERK1/2 and p65 activation, and acetylcholine levels were only detected in female hippocampus exposed to either intermediately or highly polluted eels. Sex selective effects were also detected with regard to memory, the only altered cognitive function. Thus, middle-aged females, but not males, perinatally exposed to either intermediately or highly polluted eels take longer to locate the escape platform, spend considerably less time in the platform and perform less visit to the platform in the retention test. Our results suggest perinatal programming of hippocampal-dependent memory deficit by inflammation in middle-aged offspring, in sex and dose dependent manner.